Millennium Intelligence: Understanding and Conducting Competitive Intelligence in the Digital Age - Miller, Jerry P. (Journal of Sustainable Competitive Intelligence, 2012)
Competitive intelligence doesn’t just mean a trip to the local store to see the competition’s finished products—it means gathering business information to gain an advantage in a legal and ethical manner. This book teaches what competitive intelligence is, what a company needs to have a successful intelligence program, where to place an intelligence program, and what sources to use and not use for intelligence. Technology, analysis, and security issues of intelligence are also identified and explored. Book Description Leonard Fuld (Foreword) Publication Date: June 1, 1999. Clique Aqui